Yoghurts in Infants' Nutrition: Opportunities of Infectious and Non-Communicable Diseases' Prevention - Irina A. Belyaeva; Elena P. Bombardirova; Tatyana V. Turti ("Paediatrician" Publishers LLC, 2023)
This review provides data on the use of yogurts in infants' nutrition. The properties of these fermented milk products and associated urgent and delayed sanogenetic effects are described. The experience of yogurts (enriched with pre- and probiotics) implementation in the nutrition therapy of children who have undergone infectious diseases is shown. The yogurt usage for intestinal microbiota disorders correction in children with functional digestive disorders and chronic somatic pathology is discussed.